Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1103/physrevc.86.055203
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel parametrization ofπNscattering amplitudes and extraction of resonance parameters

Abstract: We present results of a new multichannel partial-wave analysis for πN scattering in the c.m. energy range 1080 to 2100 MeV. This work explicitly includes ηN and KΛ channels and the single pion photoproduction channel. Resonance parameters were extracted by fitting partial-wave amplitudes from all considered channels using a multichannel parametrization that is consistent with S-matrix unitarity. The resonance parameters so obtained are compared to predictions of quark models.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
127
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(139 citation statements)
references
References 45 publications
(74 reference statements)
12
127
0
Order By: Relevance
“…In 2012, the observations reported in [1,3,6] were introduced into the Review of Particle Properties (RPP) under the heading of a new one-star nucleon resonance N (1685) [11] but was removed from the listings in the most recent issue of RPP [12]. The interpretation of the structure as narrow resonance was supported by further studies [13][14][15][16], the results reported in [17] were ambiguous. In a study of the helicity asymmetry of the reaction γp → ηp, no evidence for N (1685) was found [18].…”
mentioning
confidence: 72%
“…In 2012, the observations reported in [1,3,6] were introduced into the Review of Particle Properties (RPP) under the heading of a new one-star nucleon resonance N (1685) [11] but was removed from the listings in the most recent issue of RPP [12]. The interpretation of the structure as narrow resonance was supported by further studies [13][14][15][16], the results reported in [17] were ambiguous. In a study of the helicity asymmetry of the reaction γp → ηp, no evidence for N (1685) was found [18].…”
mentioning
confidence: 72%
“…20b is the original scattering-length fit [137] to the older results. This clearly fails to reproduce the new data close to threshold but, on the other hand, a parameterization of the S 11 (1535) resonance [81] describes well the forward dip in |f | 2 . However, other masses and widths for the S 11 resonance give an equally good description so that these data are not precise enough to tie down the resonance parameters accurately.…”
Section: η Production In πN Collisionsmentioning
confidence: 85%
“…Various scenarios have been suggested in the literature for the narrow structure in the neutron excitation function. They range from different coupled-channel effects of known nucleon resonances [70,76], interference effects in the S 11 partial wave [77,46], effects from the opening of strangeness thresholds [78], to intrinsically narrow states [73,77,79,80,81]. The available data are still insufficient for an unambiguous analysis.…”
Section: Photoproduction Of η-Mesons Off Nucleonsmentioning
confidence: 99%
See 2 more Smart Citations